A Comparison Study of Antiultraviolet and Sustained Release Properties of Polydopamine/Avermectin Microcapsule and Microsphere. (30th December 2018) - Shen, Zhichuan; Zhou, Xinhua; Qiu, Huina; Xu, Hua; Chen, Huayao; Zhou, Hongjun
Abstract : By using dopamine (DA) as the monomer, the model drug avermectin (AVM) was loaded on polydopamine microspheres (AVM/PDAMS) and polydopamine microcapsules (AVM@PDAMC) by the method of impregnation and encapsulation, respectively. The materials' structures were systematically characterized using Fourier transform infrared spectroscopy (FTIR), zeta potential analysis, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The comparison of antiultraviolet capability as well as release behaviors under different pH values of the materials were studied. The results showed that a spherical appearance was observed from both materials. The use of AVM/PDAMS and AVM@PDAMC made the decomposition temperature of AVM increase to 235°C and 245°C, respectively. After being exposed to ultraviolet light for 1400 min, the residual ratios of AVM of AVM/PDAMS and AVM@PDAMC were 42% and 54%, respectively. Both AVM/PDAMS and AVM@PDAMC showed acid sensitivity. AVM/PDAMS and AVM@PDAMC took about 13 h and 60 h to reach the release rate of 50% under pH 3. The release process of AVM/PDAMS could be explained by the Weibull model at pH 3, while the release behavior of AVM@PDAMC fitted the Baker–Lonsdale equation. At pH 7 and pH 9, both of the delivery materials followed the Korsmeyer–Peppas model and belonged to the Fick diffusion.